Technological Activities in CEE Countries: A Patent Analysis for the Period 1980-2009 - Iciar Dominguez Lacasa; Alexander Giebler (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
The aim of this paper is to analyze the technological activities of Central and Eastern European (CEE) economies and to compare them with the technological activities of other world regions. Using data from the EPO World Wide Statistical Database for the period 1980-2009 the analysis is based on counts of priority patent applications over time. In terms of priority patent applications, CEE reduced its technological activities drastically in absolute and per capita terms after 1990. The level of priority patent applications in this world region maintained more recently a stable level below the performance of EU15, South EU and the former USSR. In what concerns technological specialization, the results suggest a division of labor in technological activities among world regions where Europe, Latin America and the former USSR are mainly specializing in sectors losing technological dynamism in the global patent activities (Chemicals and/or Mechanical Engineering) while North America, the Middle East (especially Israel) and Asia Pacific are increasingly specializing in Electrical Engineering, a sector with strong technological opportunities.
urn:nbn:de:gbv:3:2-27008
Keywords: O30; O57; 330; CEE; patent indicators; priority counts; patstat; specialization